2020
DOI: 10.1055/a-1096-0913
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Respiratory Muscle Training on Patients’ Recovery after Lung Resection

Abstract: This prospective experimental study aimed to compare effects of 3 different home-based postoperative respiratory muscle training protocols – inspiratory, expiratory and combined, in the patients’ postoperative recovery, regarding safety and respiratory muscle function, pulmonary function, physical fitness, physical activity (PA), dyspnoea and quality of life (QoL). Patients were divided in four groups Usual Care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…In addition, previous research has shown that breathing training can alleviate the symptoms of dyspnea and prolong survival time [8]. Respiratory training can relieve pain by guiding patients to consciously prolong the time of spontaneous breathing and controlling abdominal ups and downs to carry out regular breathing exercise [9,10]. Therefore, the purpose of this study was to explore the effect of respiratory training in relieving postoperative pain in patients with spinal nerve root entrapment syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, previous research has shown that breathing training can alleviate the symptoms of dyspnea and prolong survival time [8]. Respiratory training can relieve pain by guiding patients to consciously prolong the time of spontaneous breathing and controlling abdominal ups and downs to carry out regular breathing exercise [9,10]. Therefore, the purpose of this study was to explore the effect of respiratory training in relieving postoperative pain in patients with spinal nerve root entrapment syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…One hundred thirteen studies were excluded for different reasons (see exclusion criteria). Finally, nine studies were included in the review16 31–37 (figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Selected studies had been published between 2012 and 2020. Four studies had been conducted before surgery treatment,31–34 another four after surgery35–37 or other treatments,16 and only one during radiotherapy 38. In those studies, 363 patients participated in IMT intervention; 87.4% of them were finally analysed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations